Polydopamine-assisted PDGF-BB immobilization on PLGA fibrous substrate enhances wound healing via regulating anti-inflammatory and cytokine secretion. - Xiao Yang; Peng Zhan; Xiuyan Wang; Qiushuang Zhang; Yi Zhang; Haitao Fan; Ranwei Li; Ming Zhang (PLoS ONE, 2020)
Platelet-derived growth factor-bb (PDGF-BB) is a potent chemokine and mitogen for fibroblasts, keratinocytes, and vascular endothelium in the injured area, believed to be effective in wound healing. However, the short half-life of PDGF-BB and its rapid release from the wound surface limited its efficacy in vivo and vitro. To evaluate the wound healing effects of dorsal skin in SD rats with polydopamine-assisted immobilized PDGF-BB on PLGA nanofibrous substrate. First, the effects of pDA-coating and PDGF-BB immobilization on the morphology, compositions, and hydrophilicity of substrates were evaluated in details. Second, the wound healing effect of pDA/PLGA/PDGF-BB substrate was assessed in the dorsal skin of SD rats. Last, the cytokine analysis by ELISA method was employed to evaluate the advantages of pDA/PLGA/PDGF-BB substrate on anti-inflammatory, angiogenesis, and cellular proliferation. This method significantly improved the immobilization amount and stability of PDGF-BB on the substrate (p<0.01), further improved the hydrophilicity of substrates (p<0.05). Furthermore, the wound closure process was much more accelerated in the pDA/PLGA/PDGF-BB group (p<0.05). H&E and CD31 staining informed that the wound treated by pDA/PLGA/PDGF-BB substrate showed a high degree of regeneration and angiogenesis. The cytokine analysis showed that pDA significantly reduced the high level of inflammatory cytokines such as TNF-α (p<0.05). And the immobilized PDGF-BB significantly elevated the level of TGF-β and VEGF (p<0.05). The pDA/PLGA/PDGF-BB substrate showed great therapeutic effect on wound healing compared with other control groups via regulating anti-inflammatory, angiogenesis, and cellular proliferation. Absolutely, this report offered an available novel method for skin regeneration.